AB0364 A Novel Approach for Rheumatoid Arthritis: Results of The Ongoing Clinical Trials with The Fully Human Immunocytokine Dekavil (F8-IL10). (15th July 2016) - Galeazzi, M.; Voll, R.; Sebastiani, G.; Bazzichi, L.; Viapiana, O.; Dudler, J.; Sarzi-Puttini, P.; Selvi, E.; Iuliano, A.; Pedretti, M.; Giovannoni, L.; Bindi, I.; et al.
Abstract : Background: F8-IL10 (Dekavil) is a human immunocytokine composed of the vascular targeting antibody F8, specific to the extradomain A of fibronectin, fused to the cytokine interleukin-10. F8-IL10 is being investigated in a dose-finding, PK phase Ib study and in a randomized, double blind, placebo-controlled phase II study, as a new therapeutic strategy for rheumatoid arthritis (RA). Objectives: The primary objective of the phase Ib study is to determine the safety, tolerability and MTD of Dekavil in combination with methotrexate (MTX). The primary objective of the phase II study is to assess the superiority of Dekavil plus MTX over MTX by measuring the mean change from baseline of DAS28-CRP. Immunogenicity of F8-IL10 and its PK and PD profile will also be explored. Methods: Patients with active RA despite MTX therapy and who failed anti-TNFα treatment are the target population of both studies. In the phase Ib, cohorts of 3–6 patients are treated with escalating doses of Dekavil (6, 15, 30, 60, 110, 160, 210, 300, 450 and 600 μg/kg) in combination with a fixed dose of MTX (10–15 mg). In the phase II, patients are randomized to Dekavil 30 or 160 μg/kg plus MTX or placebo plus MTX. Dekavil is administered by s.c. injection once weekly for a maximum of 8 weeks in both studies. Results: The first 9 cohorts of the phase Ib study have been completed, 32 patients were treated and 31 are evaluable for DLT. One DLT (G2 purpura) was observed in one patient of the 9th cohort. The same patient had G1 thrombocytopenia and G3 ALT increase. Both events were considered related to the study drug and resolved within ten days. Neither SUSAR nor treatment-related deaths occurred. Mild injection site reactions were reported in 59% of patients and 2 cases of anemia (G2 and G3) were considered related to the study drug. All adverse reactions resolved after the end of treatment. Currently, the MTD has not been reached and the 600 μg/kg dose is ongoing. To date, 59.3% of the 27 patients analyzed for efficacy had ACR and EULAR responses, 29.6% and 11.1% had ACR50 and ACR70, respectively, at the low dosages of 15, 30 and 60 μg/kg. Two patients benefited from ACR70 response for 12 months after the last drug administration. In the phase II study, 13 out of 87 patients have been enrolled so far. To date, neither SUSAR nor treatment-related deaths were recorded. Conclusions: The promising safety and efficacy results, even at low dosages, of Dekavil in the phase Ib study led to the start of the phase II study to verify the efficacy of Dekavil in combination with MTX in the same patient population. The currently available data suggest that the targeted delivery of IL-10 to the sites of inflammation is a promising therapeutic approach for RA. Disclosure of Interest: M. Galeazzi: None declared, R. Voll: None declared, G. Sebastiani: None declared, L. Bazzichi: None declared, O. Viapiana: None declared, J. Dudler: None declared, P. Sarzi-Puttini: None declared, E. Selvi: None declared, A. Iuliano: None declared, M. Pedretti Employee of: Philogen, L. Giovannoni Employee of: Philogen, I. Bindi Employee of: Philogen, C. Bettini Employee of: Philogen, N. Ravenni Employee of: Philogen, J. Wilton Employee of: Philogen, P. Zufferey: None declared, G. Ferraccioli: None declared, R. Caporali: None declared, C. Specker: None declared, J. Wollenhaupt: None declared, D. Neri Shareholder of: Philogen